Christian ethics: a review from the perspective of Al-Faruqi - Idris, Fathiyyatunnur (USIM Press, 2022)
This article reviews the writing of Ismail Al-Faruqi entitled “Christian Ethics: A Historical and Systematic Analysis of Its Dominant Ideas.” It thoroughly evaluates the origins of Judeo- Christian’s relationship and its relation with Islam. The method used is library-based research and deductive method of analyzing. This evaluation is crucial because there were distorted historical facts and certain misunderstandings in the idea of ethics and self-transformation and to the extent, Al-Faruqi introduced a new name to the Christians today which is Christianism and he also introduced a new approach to the study of religions i.e., Epochè. The distortions should be analyzed to avoid any confusion of the real and not real teachings of Jesus. Hence, this paper will identify the existing distortions and examine it with the original concept derived from the Islamic perspective which eventually harmonizes the ultimate reason of God sending down all His messengers to the earth.